Associations between tactile intimacy and sleep quality in healthy adults: A systematic review. (18th October 2021) - Dueren, Anna L.; Perach, Rotem; Banissy, Jasmine F. M.; Bowling, Natalie C.; Gregory, Alice M.; Banissy, Michael J.
Summary: Prior research suggests that different types of touch can affect sleep, but whether there is a consistent association between tactile intimacy and sleep quality is unclear. Here, we report a pre‐registered systematic review (International Prospective Register of Systematic Reviews [PROSPERO], CRD42020158683) of studies examining the association between tactile intimacy and sleep quality in healthy adults. The databases PsycINFO, PubMed, Web of Science, the Cochrane Central Register of Controlled Trials and EMBASE were searched on August 7, 2020. A total of 13 studies met the inclusion criteria and were synthesised qualitatively. Most commonly, articles researched sexual intimacy in relation to sleep quality, but some studies also investigated non‐sexual affective touch and emotionally neutral touch. Some evidence for a connection between sexual function, sexual satisfaction and masturbation with sleep quality was found; however, no evidence for an association between sexual frequency or sexual positions and sleep was found. Interestingly, studies employing more subjective approaches were more likely to report an association between touch and sleep, potentially highlighting a discrepancy between self‐reported and the objectively measurable association between touch and sleep.